Fostering student academic integration through institutional leadership in Saudi higher education - Aljendan, Aisha Yousef (Journal of Asian Scientific Research, 2025)
This study investigates the leadership styles that promote student involvement in Saudi Arabia's higher education institutions, with a particular focus on the role of university leaders. The research explores how institutional leaders facilitate student integration into academic and extracurricular activities. The study employed qualitative interviews with deans and faculty members, providing insights into how cultural factors and leadership practices influence student learning processes. Two theoretical frameworks guide this research: Situational Leadership Theory and Kahu's Conceptual Framework of Student Engagement. These models collectively explain how academic leaders motivate students through personalized communication and comprehensive institutional support systems. Results indicate that successful deans adapt their strategies according to circumstances, employing approaches that involve telling, selling, participating, and delegating to meet diverse student needs. Key practices for enhancing student success include open communication, encouragement of faculty autonomy, and the establishment of inclusive educational environments. The study enhances leadership understanding by further integrating students into the cultural context of Saudi Arabian universities, providing viable means of promoting student interaction and academic integration.